1993
DOI: 10.1016/0735-1097(93)90231-o
|View full text |Cite
|
Sign up to set email alerts
|

Physical training improves skeletal muscle metabolism in patients with chronic heart failure

Abstract: The reduction in phosphocreatine depletion and in the increase in ADP during exercise, and the enhanced rate of phosphocreatine resynthesis in recovery (which is independent of muscle mass) indicate that a substantial correction of the impaired oxidative capacity of skeletal muscle in chronic heart failure can be achieved by exercise training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
0
8

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(186 citation statements)
references
References 31 publications
5
173
0
8
Order By: Relevance
“…[15][16][17] In our study the ventilatory response to exercise (VE/VCO 2 ; EqCO 2 ) was low while the patient was on the VAD and similar to that after heart transplantation. This variable is often increased in heart failure and is considered an important prognostic marker.…”
Section: Discussionsupporting
confidence: 60%
“…[15][16][17] In our study the ventilatory response to exercise (VE/VCO 2 ; EqCO 2 ) was low while the patient was on the VAD and similar to that after heart transplantation. This variable is often increased in heart failure and is considered an important prognostic marker.…”
Section: Discussionsupporting
confidence: 60%
“…Beneficial changes in structure, metabolism and biochemical function of skeletal muscle have been observed after training, culminating in an increase in oxidative capacity ( Adamopoulos et al 1993;Sullivan et al 1988), but none of these aspects were investigated in this study.…”
Section: ~~-------------------------------------mentioning
confidence: 99%
“…Further investigations by Adamopoulos et al (1993) of the patients involved in the study by Coats et al (1992) found that the oxidative capacity of skeletal muscle, as measured by ADP and phosphocreatine content, improved with eight weeks of training. Coats et al (1992) also found evidence that training enhanced vagal activity and decreased sympathetic activity, similar to that seen in healthy subjects.…”
Section: Exercise Training Programmesmentioning
confidence: 99%
“…These favourable changes result in an important reduction in dyspnoea and in a small decrease in fatigue, and therefore in an increase in the capacity to perform physical activity. 27 In the medium range, increased physical activity, particularly if it includes exercise training, would improve the structure and function of skeletal muscle [29][30][31][32][33] and would reduce excess ventilation, [33][34][35][36] thereby mitigating dyspnoea and fatigue further.…”
Section: Introductionmentioning
confidence: 99%